Ijtihad Sebagai Pilar Kelangsungan Hukum Islam di Tengah Perubahan Zaman - Somantri, Yayan; Sucipto, Imam (Yayasan Cendekia Gagayunan Indonesia, 2024)
Ijtihad is a fundamental pillar in maintaining the continuity of Islamic law, ensuring its relevance amidst the challenges of changing times. Derived from the term jahada, meaning